Nanomagnetos moleculares contendo fenilenobis (oxamato), bipiridina e bis(2-piridilcarbonil)-amida - Tatiana Renata Gomes Simoes (2010)
In this work, low dimensional molecular magnets were synthesized andcharacterized and their magnetic properties were investigated. Initially, the novel compound {[Cu(bipy)]3[Cu2(mpba)2]}(ClO4)2.11H2O (where mpba is metaphenylene-bis(oxamate) and bipy is 2,2- bipyridine) was synthesized, being a paramagnetic compound that exhibits an antiferromagnetic coupling. At 300 K, the mT for this compound assumes the value equal to 2.01 emu K mol-1(m is the molar magnetic susceptibility), that is in accordance to the proposed formula. The chain {[Cu(bipy)2ClO4]ClO4}n was also formed, as a sub product, and exhibits an antiferromagnetic behavior owed to the spin coupling between the metallic ions into the perchlorate bridges. The structure of the novel compound [Ni3(mpba)2(bipy)3].3DMSO.5H2O was determined by single crystal X-ray diffraction, being the cluster characterized as three Ni(II) ions in a distorted octahedrical geometry. Afterwards, in the second part of the present work, crystals of the {[Cu(bipy)][Cu(opba)]}2, where opba means ortophenilenobis(oxamate)), were obtained by using a different approach from that described in the literature. In addition, the novel compound {[Ni(bipy)][Cu(opba)]} was synthesized. Through the direct reaction, by simultaneous mixing of the reagents, the pentanuclear {[Cu(opba)(Co(bipy)]2Co}Cl2.DMSO.H2O and the heptanuclear {[Cu(opba)(Cu(bipy)]3Co}Cl2.DMSO.2H2O systems were prepared. Finally, it was synthesized the totally closed cluster {[Cu(bpca)]4[Cu2(mpba)2]}.10H2O, being bpca = anion (bis(2-piridilcarbonil)-amide), and another cluster of theLi5{[Cu(bpca)]3[Co2(mpba)3]}.10H2O containing three free coordinationpositions. Crystals of the compound [Cu4(bpca)4(mpba)] without threecrystallization water molecules, in contrast to that reported in the literature, were also isolated.